Capacidad vehicular y nivel de servicio con la metodología Highway Capacity Manual (HCM) - Surichaqui, Mercedes (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
This book is an adaptation of an investigation presented to the Universidad Nacional Hemilio Valdizán, whose objective was to study the behavior of roundabouts under demand conditions and to estimate the level of service experienced in the different accesses of Parque Ovalo Huancavelica, Junín (Peru). with the HCM 2010 (NCHRP) methodology. It was approached from a descriptive-explanatory methodology with a correlational design, with a non-probabilistic sample, selecting the intersections with high vehicular traffic in the city of the El Tambo district. The results indicate that there are sections with a higher vehicular density with a level of service "F" and sections that present a vehicular flow with a level of service "A", indicating a measure that increases the diameter inscribed in the roundabout, the delay decreases, the maneuvers usually turn left and make a U-turn, they are the most invasive movements and generate high delays.